2010
DOI: 10.1016/j.mambio.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Den preferences and denning behaviour in urban stone martens (Martes foina)

Abstract: Stone martens (Martes foina) occur in urban environments in many parts of continental Europe, where they cause a nuisance by denning in inhabited houses. We radio tracked 13 stone martens (10 females, 3 males) in two towns in southern Luxembourg during a 2-year period, in order to investigate den preferences and patterns of den use. We predicted that urban martens would make more use of buildings and less use of natural den sites than do their rural counterparts. All martens used multiple den sites but use was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 18 publications
3
53
0
4
Order By: Relevance
“…They provide refuge against predators and protection against harsh climatic conditions (Buskirk 1984;Zalewski 1997a). Their characteristics, use, and distribution have been the subject of numerous studies (e.g., Magoun and Copeland 1998;Kowalczyk et al 2000Kowalczyk et al , 2004Zalewski 1997b;Cantú-Salazar et al 2009;Herr et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They provide refuge against predators and protection against harsh climatic conditions (Buskirk 1984;Zalewski 1997a). Their characteristics, use, and distribution have been the subject of numerous studies (e.g., Magoun and Copeland 1998;Kowalczyk et al 2000Kowalczyk et al , 2004Zalewski 1997b;Cantú-Salazar et al 2009;Herr et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Diseased coyotes were also more likely to seek out anthropogenic shelter than healthy coyotes. Although many urban‐adapted mammals use houses as bedding and den sites (e.g., raccoons [ Procyon lotor ], Gross et al ; brushtail possums [ Trichosurus vulpecula ], Statham and Statham ; and stone martens, Herr et al ), we found that the use of shelter under buildings was dependent on coyote condition. Coyotes with mange were much more likely to bed under houses than healthy coyotes, perhaps to avoid the energetic costs of low temperatures because they suffered from poor coat quality and potentially compromised thermoregulation.…”
Section: Discussionmentioning
confidence: 61%
“…However, this tendency is highly variable among species (Bateman and Fleming ) and individuals (Knopff et al ). Encounters with people and subsequent management action were more likely for brown bears ( Ursus arctos ) that became highly habituated to human infrastructure, such as buildings (Rauer et al , Elfström et al ), which can also be used as den sites by stone marten ( Martes foina ; Herr et al ) and a variety of urban carnivores (Bateman and Fleming , Lowry et al ). Many carnivore species can also make use of anthropogenic food (Contesse et al , Newsome et al ), and the development of food‐conditioned animals who associate people with food usually results in conflict (Herrero , McCarthy and Seavoy ).…”
mentioning
confidence: 99%
“…For example, over 50 % of raccoon dens occur in human-made structures (Hoffmann and Gottschang 1977;O'Donnell and DeNicola 2006), such as attics, chimneys, garages, sheds, ventilation ducts, furniture (Adams and Lindsey 2010), and sewers (Hoffmann and Gottschang 1977). Other mammals that use human-made structures are striped field mice ( Apodemus agrarius) (Gliwicz et al 1994), fox squirrels ( Sciurus niger) (McCleery et al 2007), stone martens ( Martes foina) (Herr et al 2010), skunks ( Mephitis spp.) (Rosatte et al 2010), and red foxes ( Vulpes vulpes), which appear to be less tolerant of human presence and den mainly in abandoned structures .…”
Section: Use Of Human Structuresmentioning
confidence: 99%